Should the EU pursue a strategic ginseng policy? Trade dependency in the brave new world of geopolitics - Oscar Guinea; Vanika Sharma (European Centre for International Political Economy (ECIPE), 2022)
Political leaders all over the world are calling for strategic autonomy. The removal of critical trade dependencies has become a guiding principle in most policy proposals, including the EU's new industrial strategy. In making these decisions, it is important for policymakers to understand the reasons behind why shortages of critical goods and technologies have emerged in the first place. The instruments that new policies cerate should respond to real problems, not invented ones. For instance, if shortages are due to temporary mismatches of supply and demand, most of them will be fixed without the need of any policy intervention. On the other hand, shortages can also be engineered by countries using their dominance in the production of certain goods to coerce other countries. As the EU experienced first-hand after the Russian war on Ukraine in 2022, the concentration of market power in the production of any product carries geopolitical risks. For that purpose, it is crucial to understand the nature of trade dependencies. This policy brief presents indicators and a conceptual framework to measure trade dependency.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Rohstoffversorgung; Rohstoffpolitik; Autonomie; EU-Industriepolitik; EU-Staaten